2022
DOI: 10.1111/1365-2745.13905
|View full text |Cite
|
Sign up to set email alerts
|

Flowering overlap and floral trait similarity help explain the structure of pollination networks

Abstract: 1. Co-flowering communities are usually characterized by high plant generalization but knowledge of the underlying factors leading to high levels of generalization and pollinator sharing, and how these may contribute to network structure is still limited.2. Flowering phenology and floral trait similarity are considered among the most important factors determining plant generalization and pollinator sharing.However, these have been evaluated independently even though they can act in concert with each other. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 108 publications
0
16
0
Order By: Relevance
“…To evaluate the effect of the spatial arrangement of modulating the opposing effects of plant-plant interaction and plant-pollinator interaction of plant reproductive success, we used Structural Equation Models (SEMs) (Suárez-Mariño et al ., 2022) with a multigroup analysis context. The multigroup context was used to further test the hypothesis that different processes affect plant reproductive success at different spatial scales.…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the effect of the spatial arrangement of modulating the opposing effects of plant-plant interaction and plant-pollinator interaction of plant reproductive success, we used Structural Equation Models (SEMs) (Suárez-Mariño et al ., 2022) with a multigroup analysis context. The multigroup context was used to further test the hypothesis that different processes affect plant reproductive success at different spatial scales.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, z value for each species can be considered as its modularity contribution in the network (Suaŕez-Mariño et al, 2022). Similar with the previous studies, weighted versions of z and c were calculated using species strength instead of species degree here (Watts et al, 2016).…”
Section: Network Metrics At the Species Levelmentioning
confidence: 99%
“…This finding indicated other unmeasured traits such as phenological factors, to some degree, accounting for the nested structure of plant-pollinator network in the study community. For instance, Suaŕez-Mariño et al (2022) showed that an increase in flowering overlap led to a higher degree of plant generalization and, in turn, with consequences for network nestedness. Furthermore, pollinators may play a more active role in the definition of interaction identity than plants because of pollinator mobility (Bascompte and Jordano, 2007).…”
Section: Different Influences Of Phylogenetically Independent and Con...mentioning
confidence: 99%
See 2 more Smart Citations